PENCARIAN GURU LES PRIVAT DI SEMARANG BERBASIS WEB SEARCH PRIVATE TUTORS WEB-BASEDIN SEMARANG - Mahardani, Irna; Mariana, Novita (Information Technology and Telematics, 2018)
ABSTRACK A variety of ways parents get their children to get high marks in their lessons, from starting to buy textbooks to finding private tutors. Private course have become a necessity for parents who want their children to be proficient in a particular lesson. With private lessons, children can better understand difficult material with a more relaxed method, comfortable, easy to understand, not awkward, and not boring. However, there are some problems experienced by parents or students in finding the best private tutors, such as the length of time to find private tutors, locations and schedules for learning processes that are difficult to adapt between students and prospective private tutors, and lack of information about achievement , competence, and educational background of private tutor tutor itself. From these problems comes a web-based system in which there is a lot of information about the data self-complete teacher so that it can be a container for private tutors and students in facilitating the search process. With this private tutor tutoring system is expected to help the search process of private teachers and students to be more effective and efficient. This system is built using prototype system development method, system design that is DFD, as well as PHP programming language and MySQL database.